Inventarisasi Pteridophyta Epifit dan Asosiasi Pohon Inangnya di Hutan Desa Paninggaran, Pekalongan - Dewi, Lussana Rossita; Satriani, Slamet; Rahma, Anisa; Arimah, Sinta (Jurnal Ilmiah Biologi UMA (JIBIOMA), 2025)
The purpose of this study was to identify various types of epiphytic Pteridophytes and their host trees. This study used an exploration method or direct exploration method and obtained the types of Pteridophytes found in the Paninggaran Village Forest. Plant observations were carried out by observing morphological characters in plants including leaf shape, leaf color, leaf length, and leaf width. The identification results were then matched with references, namely Flora books, Plant Taxonomy, and Plant Morphology. The application used Google Lens and the Global Biodiversity Information Facility/GBIF website. Plant observations were carried out by observing morphological characters in plants including leaf shape, leaf color, leaf length, and leaf width. Based on the results of the study, 10 species were found in the Paninggaran Village Forest and divided into 7 families and 5 types of host plants.